Peanut Plant Development Strategy as a Leading Commodity in South Tinangkung District, Banggai Islands Regency - Sariani; Anas Boceng; Saida Saida; Ilham Ladonu (CELEBES Agricultural, 2023)
Agricultural development aims to improve the living standards of farmers and the welfare of their people. The prospects for the development of peanut farming business are very bright in order to increase the income and welfare of farmers, so there is a need for a strategy in the development of peanuts as a leading commodity. Thus, this study aims to develop a strategy for developing peanuts as a leading commodity in South Tinangkung District, Banggai Islands Regency. The research was conducted from June to November 2022 in South Tinangkung District, Banggai Islands Regency. The data used in this study is primary data. Primary data were obtained by conducting structured interviews and direct observations from certain natural places by circulating questionnaires to respondents. Furthermore, the research used the SWOT method, namely SO (Strength-Opportunity), WO (Weakness-Opportunity), ST (Strength-Threats), and WT (Weakness-Threats). The results obtained in this study are that the development of peanut crop commodities in South Tinangkung District is in the second tier (diversification). so that the most appropriate strategy to be applied is Strategy-ST, thus the main strategy for the development of peanuts as a superior commodity is to utilize the experience of farmers in farming peanut crops with the ability to carry out land management to overcome the shortage of Agriculture machinery needs, in addition to that, it can maximize the role of Agricultural cooperation and can reduce high labor wages.